2018
DOI: 10.1371/journal.pone.0189926
|View full text |Cite
|
Sign up to set email alerts
|

A strong summer phytoplankton bloom southeast of Vietnam in 2007, a transitional year from El Niño to La Niña

Abstract: Summer upwelling occurs frequently off the southeast Vietnam coast in the western South China Sea (SCS), where summer phytoplankton blooms generally appear during June-August. In this study, we investigate inter-annual variation of Ekman pumping and offshore transport, and its modulation on summer blooms southeast of Vietnam. The results indicate that there are low intensities of summer blooms in El Niño years, under higher sea surface temperatures (SST) and weaker winds. However, a different pattern of monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The multiple correlation coefficient (Table 2) between Chl-a and all the environmental factors (R = 0.798, p < 0.01) indicates that each of all factors impacts summer phytoplankton blooms in the WSCS. However, in offshore waters, ET and EPV have greater effects on summer phytoplankton blooms than any other factor, consistent with the previous studies (Liu et al, 2012;Gao et al, 2013;Tang et al, 2014;Liang et al, 2018;Zhao et al, 2018).…”
Section: Discussion Possible Environmental Factors Regulating Summer Phytoplankton Bloomssupporting
confidence: 91%
See 2 more Smart Citations
“…The multiple correlation coefficient (Table 2) between Chl-a and all the environmental factors (R = 0.798, p < 0.01) indicates that each of all factors impacts summer phytoplankton blooms in the WSCS. However, in offshore waters, ET and EPV have greater effects on summer phytoplankton blooms than any other factor, consistent with the previous studies (Liu et al, 2012;Gao et al, 2013;Tang et al, 2014;Liang et al, 2018;Zhao et al, 2018).…”
Section: Discussion Possible Environmental Factors Regulating Summer Phytoplankton Bloomssupporting
confidence: 91%
“…Nutrients regulate phytoplankton growth in most WSCS areas (Zhao et al, 2005a;Zhao and Tang, 2007). Stable stratification during summer in euphotic layers inhibits nutrient transport from deeper waters (Zhao et al, 2018). Vertical transport is an important source of euphotic nutrients in oligotrophic seas (Xie et al, 2003;Jin et al, 2009;Zhao et al, 2018).…”
Section: Influence Of Upwelling Northward Current and The Northeastward Jet On Summer Phytoplankton Bloomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the distribution of PHY in 2011 reflected that the range and the value of high PHY areas in the northern gulf was greater than in 2011 and 2015, indicating that the lower sea temperature in the La Niña year was more conducive to PHY growth in the Beibu Gulf [61]. In the La Niña phase, the wind strengthened, resulting in an increase in CV and seawater mixing, so the concentration of PHY increased [62,63]. From the results of the model simulated outputs (Figures 9-11), we found that the La Niña year of 2011 had lower TEM in general, especially in the northern gulf, and the area of high PHY was larger than that of 2013 and 2015 in the northeastern gulf, but that it moved to south.…”
Section: The Climate Effectmentioning
confidence: 97%
“…The same study also pointed out the need for more representation of studies involving ecosystems in subtropical and tropical latitudes. Temporal patterns in bloom dynamics also can be linked to recurring changes in key environmental conditions at multiyear intervals, such as El Niño/La Niña cycles that affect rainfall levels and in turn alter external nutrient loads, water residence times and a range of other water quality conditions, including plankton dynamics (Lipp et al, 2001;Zhu et al, 2017;Zhao et al, 2018;Jiménez-Quiroz et al, 2019). For example, peaks in the abundance of the globally distributed toxic dinoflagellate Pyrodinium bahamense have been correlated to high rainfall associated with El Niño periods in Florida and the Indo-Pacific (Phlips et al, 2006(Phlips et al, , 2020Usup et al, 2012).…”
Section: Introductionmentioning
confidence: 99%